KNOCKOFF BRAND SEBAGAI STRATEGI PEMASARAN KNALPOT “PALSU” PURBALINGGA - Lutfitona Ridho Pambudi; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2018)
Exhaust system is one of part in motor vehicles that most widely changed from the standard model. One of the reason why vehicle owners change their standard exhaust system to a racing or aftermarket model is because of the looks of racing exhaust is more attractive and cooler. Another reason is the performance of the vehicle is increasingly changed with aftermarket exhaust system. Purbalingga regency is the biggest exhaust producer that widely known with their fake exhaust products. A sales data of 2016 shows that fake exhaust selling is higher than original lables with the quality that tends to be similar. This research is aimed to know the relations between brand image and product quality to consumer's decision in buying Purbalingga exhaust system. The type of research that is used is explanatory research and the sampling technique is nonprobability sampling technique with purposive sampling method. The data collection uses interview questionnaires and the samples are 100 respondents of Purbalingga exhaust system consumer. The result of this study shows that the relation of brand image and product quality variables have a strong and positive influence to consumer decisions, whether it is a original lable or fake lable exhaust system.